Electrochemical Grafting of Chitosan on Polyaniline and its Characterization - Rai, Deepshikha; Neupane, Shova; Oli, Hari Bhakta; Gupta, Dipak K.; Yadav, Amar P. (Journal of Nepal Chemical Society, 2018)
Available witn full text.